(Photo)convert to pooled visual screening. Issue 6 (16th June 2020) - Ivanova, Elena; Khmelinskii, Anton
Abstract : Pooled genetic screening is a powerful method to systematically link genotype to phenotype and gain insights into biological processes, but applying it to visual phenotypes such as cell morphology or protein localization has remained a challenge. In their recent work, Fowler and colleagues (Hasle et al, 2020) describe an elegant approach for high‐throughput cell sorting according to visual phenotypes based on selective photoconversion. This allows combining the advantages of high‐content phenotyping by fluorescence microscopy with the efficiency of pooled screening to dissect complex cellular processes. Abstract : The application of pooled genetic screens to link genotypes to visual phenotypes has remained a challenge. In their recent work, Fowler and colleagues describe an approach for high‐throughput cell sorting based on visual phenotypes in cells.